To determine the role of TRIT1 in the diagnosis, prognosis and immunoinvasion of liver hepatocellular carcinoma - Xinyu Niu; Xinyu Niu; Xiaona Pan; Guifang He; Chao Xuan; Qingwu Tian; Yuan Yuan; Jingqiu Chen; Jingqiu Chen; Yaqi Song; Yaqi Song; Yujuan Tang; et al. (Frontiers in Immunology)
BackgroundTRIT1 is identified as a potential tumor suppressor gene that may be involved in tumor development. Existing research indicates that TRIT1 is significant in the development of certain cancers. However, its specific role in liver cancer remains elusive.MethodsExpression profiles and clinical data of liver hepatocellular carcinoma (LIHC) patients were retrieved from The Cancer Genome Atlas (TCGA) database. The TRIT1 gene levels between LIHC tissues and normal tissues were compared using the Wilcoxon rank-sum test. Additionally, TRIT1 expression levels were further examined via reverse transcription quantitative polymerase chain reaction (RT-qPCR). Functional enrichment analysis was performed to elucidate the biological pathways associated with TRIT1. Immune cell infiltration patterns were evaluated using single-sample gene set enrichment analysis (ssGSEA). The methylation status of the TRIT1 gene were analyzed using the UALCAN and MethSurv databases. Cox regression analysis and Kaplan-Meier (KM) methods were employed to determine the prognostic value of TRIT1. To create a practical tool for predicting overall survival over time, a nomogram was constructed.ResultsThe analysis revealed that TRIT1 expression is significantly higher in LIHC tissues compared to normal tissues. Furthermore, elevated TRIT1 levels were found to be associated with specific subtypes of LIHC, including T3 and stage III. Importantly, TRIT1 overexpression was identified as a negative prognostic marker for overall survival in LIHC patients. Additionally, hypermethylation of the TRIT1 gene was associated with poor prognosis. Moreover, this study demonstrated that high TRIT1 levels were correlated with reduced levels of cytotoxic immune cells in the tumor microenvironment, including B cells, cytotoxic cells, and plasmacytoid dendritic cells (pDCs).ConclusionsThis study provides the first evidence that the presence of TRIT1 can serve as a reliable marker for diagnosis and prognostication of hepatocellular carcinoma. Moreover, TRIT1 emerges as a critical indicator of the potential for cancer infiltration and invasion of the immune system, holding significant implications for the development of targeted therapies for hepatocellular carcinoma.